Case Report: Locally advanced clear cell renal cell carcinoma with pathological complete response following nephrectomy and thrombectomy after nivolumab and cabozantinib treatment - Yoshioka, Hayato; Kitano, Hiroyuki; Kobatake, Kohei; Sekino, Yohei; Ishikawa, Akira; Goto, Keisuke; Goriki, Akihiro; Hieda, Keisuke; Arihiro, Kouji; Hinata, Nobuyuki (Frontiers in Oncology, 2025)
The recent introduction of systemic anticancer therapies (SACT) and immune checkpoint inhibitors in cancer management has led to reports on the usefulness of deferred cytoreductive nephrectomy (dCN) following vascular endothelial growth factor receptor-tyrosine kinase inhibitor and immune checkpoint inhibitor combination therapy (VEGFR-TKI + ICI) for metastatic renal cell carcinoma (RCC), as well as nephrectomy after VEGFR-TKI + ICI combination therapy for initially unresectable locally advanced RCC. However, the optimal approach to SACT and the suitable patient profiles for these approaches remain unclear. We report the case of a 73-year-old man with stage III RCC accompanied by venous invasion, initially diagnosed as unresectable. Following VEGFR-TKI + ICI combination therapy with nivolumab and cabozantinib, he underwent nephrectomy and thrombectomy, resulting in a pathological complete response (pCR). The patient was diagnosed with left RCC after a tumor measuring 80 × 60 mm with tumor thrombus in the left renal vein was confirmed (cT3aN0M0), and subsequent percutaneous biopsy performed prior to embolization revealed clear cell histology. The tumor size was reduced following treatment with nivolumab and cabozantinib. Robot-assisted left nephrectomy was subsequently performed. Postoperative pathology tests confirmed no malignant findings, suggesting pCR. Conventionally, cytoreductive nephrectomy is performed prior to SACT; however, there has been an increase in dCN use. In this case, the combination of nivolumab and cabozantinib led to the pCR of unresectable RCC, suggesting that VEGFR-TKI + ICI combination therapy may exert a strong tumor-reducing effect and could contribute to the establishment of an optimal SACT regimen prior to dCN or nephrectomy in patients with locally advanced RCC.